Dynamic contrast‐enhanced MRI in mouse tumors at 11.7 T: comparison of three contrast agents with different molecular weights to assess the early effects of combretastatin A4. (November 2014) - Fruytier, A.‐C.; Magat, J.; Neveu, M.‐A.; Karroum, O.; Bouzin, C.; Feron, O.; Jordan, B.; Cron, G. O.; Gallez, B.
<x xml:space="preserve">Abstract</x> Dynamic contrast‐enhanced (DCE)‐MRI is useful to assess the early effects of drugs acting on tumor vasculature, namely anti‐angiogenic and vascular disrupting agents. Ultra‐high‐field MRI allows higher‐resolution scanning for DCE‐MRI while maintaining an adequate signal‐to‐noise ratio. However, increases in susceptibility effects, combined with decreases in longitudinal relaxivity of gadolinium‐based contrast agents (GdCAs), make DCE‐MRI more challenging at high field. The aim of this work was to explore the feasibility of using DCE‐MRI at 11.7 T to assess the tumor hemodynamics of mice. Three GdCAs possessing different molecular weights (gadoterate: 560 Da, 0.29 mmol Gd/kg; p846: 3.5 kDa, 0.10 mmol Gd/kg; and p792: 6.47 kDa, 0.15 mmol Gd/kg) were compared to see the influence of the molecular weight in the highlight of the biologic effects induced by combretastatin A4 (CA4). Mice bearing transplantable liver tumor (TLT) hepatocarcinoma were divided into two groups (n = 5–6 per group and per GdCA): a treated group receiving 100 mg/kg CA4, and a control group receiving vehicle. The mice were imaged at 11.7 T with a T1‐weighted FLASH sequence 2 h after the treatment. Individual arterial input functions (AIFs) were computed using phase imaging. These AIFs were used in the Extended Tofts Model to determine Ktrans and vp values. A separate immunohistochemistry study was performed to assess the vascular perfusion and the vascular density. Phase imaging was used successfully to measure the AIF for the three GdCAs. In control groups, an inverse relationship between the molecular weight of the GdCA and Ktrans and vp values was observed. Ktrans was significantly decreased in the treated group compared with the control group for each GdCA. DCE‐MRI at 11.7 T is feasible to assess tumor hemodynamics in mice. With Ktrans, the three GdCAs were able to track the early vascular effects induced by CA4 treatment. Copyright © 2014 John Wiley & Sons, Ltd.